(untitled) (IPS Journal of Public Health, 2025)
Vibrio cholerae, a prominent species within the Vibrio genus, is commonly found in aquatic environments such as streams. This bacterium has garnered significant attention due to its role in causing human infections and its increasing involvement in antibiotic resistance. Notably, a substantial proportion (approximately 80%) of antibiotic-resistant genes in V. cholerae are plasmid-encoded, contributing to the spread of resistance. This cross-sectional study investigated the prevalence of Vibrio species in streams within the Uli community. Water samples were collected from various streams and analyzed using standard microbiological techniques. The study significantly (p ≤ 0.05) identified three strains of Vibrio cholerae: VCC6 (Vibrio cholerae serovar 01 biovar Eltor strain C6709), VCP2 (Vibrio cholerae serovar O1 biovar Eltor strain P27459), and VCE7 (Vibrio cholerae strain E7946). The overall prevalence of Vibrio cholerae was 44.00%, with VCC6 being the most predominant strain (50.00%), followed by VCE7 (31.82%), and VCP2 (18.18%).The findings highlight the presence of pathogenic Vibrio cholerae strains in streams used by the Uli community, posing a significant public health risk. To mitigate this risk, the study recommends promoting personal hygiene, community education, and proper water treatment practices, such as thorough boiling of water before consumption. These measures can help control the transmission of Vibrio cholerae and prevent waterborne outbreaks in the community. The study’s results underscore the importance of regular water quality monitoring and public health interventions to safeguard the well-being of the community.